Head and Neck Cancer - Bruce, Brockstein.; Gregory, Masters. (Cancer Treatment and Research,, 2003)
Exciting advances are occurring in the understanding of the molecular pathogenesis of squamous head and neck cancers. Epidemiology, staging and screening, as well as premalignancy, chemoprevention and the molecular biology of head and neck cancer, lay the groundwork for the understanding of the clinical chapters that follow. Controversial treatments will be compared to the standard management of patient care. Therapy chapters are divided into stage or category specific (resectable advanced, unresectable advanced or metastatic) problems, allowing the reader to review the current standards and options for patient types or specific patients easily. Considerations of supportive care, late toxicities and quality of life, often overlooked are reviewed in detail. This is a comprehensive summary of the current state of the art research and treatment.